One-pot fabrication of fluoride-silica@silica raspberry-like nanoparticles for superhydrophobic coating. Issue 13 (October 2016) - Zhao, Zheng-Bai; Zhang, Da-Ming; Meng, Yi-Fan; Tai, Li; Jiang, Yong
Abstract: A facile and effective method to fabricate raspberry-like nanoparticles is reported in a one-pot reaction. This method consists of two steps: preparation of silica nanoparticle precursors dispersion via the Stober process and growth of the tiny functional fluoride-silica nanoparticles on the surface of silica nanoparticle precursors via the hydrolysis-condensation reaction of tetraethoxysilane (TEOS) and 1H, 1H, 2H, 2H-Perfluorodecyl triethoxysilane (HDFTES). The obtained raspberry-like nanoparticle dispersion could be spray coated onto different substrates directly with the water contact angle greater than 150° and water roll-off angle less than 4°. And the prepared coatings maintained water resistance after water jetting, sand abrasion. This method can be an effective strategy for fabricating superhydrophobic surfaces for practical industrial applications.